The honor of spies - Griffin, W. E. B. (Griffin, W. E. B. Honor bound novel, 2011)
Assigned to help a German lieutenant colonel to escape from a prisoner-of-war detention center, World War II OSS officer Cletus Frade learns of the colonel's role in a conspiracy to assassinate Adolf Hitler and must outmaneuver a plot to kill the man's Nazi-connected parents.